Vlach-language theatre: The role of supertitles as translation in endangered-language heritage performance - Christina Papagiannouli (Nalans)
During the spring and summer of 2023, I visited my hometown Veria to undertake preliminary research on endangered-language heritage performance with funding from the Welsh Government’s Taith programme. During my visit, I worked closely with the Folklore Association of Vlachs of Veria, observed their work, and participated in their heritage performance, learning not only about the communities’ cultural heritage but also about my own personal heritage. Based on empirical research, observations, personal experience and practice research, this paper focuses on the use of supertitles and multimedia projection as a translation strategy to safeguard endangered languages, traditions, and cultures. In particular, I discuss the case of Vlach-language theatre play La Câshiari (Στο Τυροκομείο / In the Dairy) by Takis Georgiou (playwright and director), performed on 28 May 2023 with Greek supertitles. Here, both the original text and translation are written by the same author simultaneously, self-translation (see Grutman & Van Bolderen, 2014), rather than translated by a different person; “an extreme case of the author/work – translator/work dialectic” (Tanqueiro, 2000, p. 63). It is then enriched by other members of the community contributions, who either identify a more appropriate Vlach word or correct the translation to allow for a clearer meaning to be made, which can be seen as an interlinear and group-dialectic approach to translation. As Geraldine Brodie (2020) notes, ‘[t]he intermedial performance of surtitles positions surtitles within new media dramaturgy, creating a form of interlinear translation’ (p. 450). Indeed, new technologies allow intermedial approaches in supertitled theatre, reaching beyond textual aspects.